Antibiotics in dental practice: The problem of irrational usage, what can we do: Mini review - Milovanović Boban; Mijatović Jelena; Tričković Vesna; Urošević Zoran; Matijević Stevo (Balkan Journal of Dental Medicine)
Antimicrobial resistance (AMR) is an escalating global health issue, with improper use in medical and dental practices being one of the contributing factors. In dentistry, antibiotics are frequently prescribed for the prevention and treatment of infections. However, excessive prescribing, improper, and irrational use have led to an increase in resistant microorganisms, jeopardizing the effectiveness of existing antibiotics. The aim of this paper was to highlight the current state of antibiotic prescribing in dental practice and present modern principles of rational use, focusing on clinical indications, appropriate selection, dosage, and duration of therapy, as well as strategies to slow the process of AMR as a pressing global problem of contemporary civilization.